Contextualising the findings - the Orkney social pedagogy evaluation - Evelyn Vrouwenfelder (Scottish Journal of Residential Child Care)
CELCIS, formerly SIRCC, has funded a series of ThemPra social pedagogy courses for residential childcare staff across Scotland. ThemPra is a small social enterprise consisting of German, English and Danish social pedagogy trainers. Their 10-day courses facilitate experiential and reflective learning, combining grounded childcare theory and social pedagogy principles and practice. Orkney local authority ran this course in 2011, cofunding delivery for a multi-agency group of 18 staff. CELCIS commissioned the Orkney training evaluation and the subsequent report was published in March 2012. The article provides a summary of the key findings which were captured over a period of 6 months. It also describes ‘what happened next’ in Orkney and considers this in terms of academic writing on learning transfer and sustainability of evaluation outcomes. A key aspect of the article is the link between the methodology of the course and its subsequent outcomes.